IDENTIFIKASI SPORA MIKORIZA VESICULAR ARBUSKULAR DARI RHIZOSFER PERKEBUNAN KARET (Hevea brasiliensis Muell arg) - khairani, Siti (Fakultas Sains dan Teknologi, 2022)
ABSTRACT Morphological characteristics of Arbuscular Mycorrhizal Fungi (AMF). This research was conducted from March to April 2021. The method used in this research is descriptive exploratory method by purposive sampling for soil sampling. While the stages of this research include: location permitting, data collection and collection in the field, determination of the location for soil sampling, soil sampling, analysis of soil properties in the laboratory, isolation of AMF spores and identification of AMF spore morphology. The results showed that the highest spore population was found through the identification of vesicular arbuscular mycorrhizae (AMF) at two rubber plantation locations, there were 16 AMF species found, namely. It belongs to the genera Glomus, Gigaspora and Acaulospora. Genus Glomus, where in the STIPAP Medan garden there were 3 morphotypes of the Glomus genus, while in the Sungai Putih plantation, PTPN III showed 13 morphotypes. Genus Glomus showed 9 morphotypes, Genus Gigaspora showed 1 morphotype and Genus Acaulospora 3 morphotypes.